2021
DOI: 10.1021/acsanm.1c01907
|View full text |Cite
|
Sign up to set email alerts
|

Review of Oxygenation with Nanobubbles: Possible Treatment for Hypoxic COVID-19 Patients

Abstract: The coronavirus disease (COVID-19) pandemic, which has spread around the world, caused the death of many affected patients, partly because of the lack of oxygen arising from impaired respiration or blood circulation. Thus, maintaining an appropriate level of oxygen in the patients’ blood by devising alternatives to ventilator systems is a top priority goal for clinicians. The present review highlights the ever-increasing application of nanobubbles (NBs), miniature gaseous vesicles, for the oxygenation of hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 221 publications
(444 reference statements)
0
22
0
Order By: Relevance
“…To this end, hyperbaric oxygen therapy [ 1006–1008 ] has been recommended, and in some cases found useful in rheumatoid arthritis [ 1009–1011 ], acute [ 1012 , 1013 ] and Long COVID [ 1006 , 1014 ]. An alternative involves O 2 nanobubbles [ 1015 ].…”
Section: Other Non-pharmacological Methodsmentioning
confidence: 99%
“…To this end, hyperbaric oxygen therapy [ 1006–1008 ] has been recommended, and in some cases found useful in rheumatoid arthritis [ 1009–1011 ], acute [ 1012 , 1013 ] and Long COVID [ 1006 , 1014 ]. An alternative involves O 2 nanobubbles [ 1015 ].…”
Section: Other Non-pharmacological Methodsmentioning
confidence: 99%
“…166 In this respect, nanobubbles (NBs), spherical stable gas-containing vesicles suspended in an aqueous solution, are an excellent nanocarrier platform for medical aid and efficient site-specific delivery of gas molecules and drugs. 167 The nanobubbles have unique features such as nanoscopic sizes, high surface-to-volume ratio, high internal pressure, long-term stability, surface charge properties, and are not agglomerated or deflated before reaching the target area. With their biocompatibility and noninvasive nature, nanobubbles are very promising nanomedicine platforms for COVID-19 treatment and next-generation biomedical applications.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…They have reported that reduced graphene oxide contents could provide synergistic effects by harvesting some respiratory electrons from the bacteria and transferring them into the O 2 nanobubbles, which leads to the formation of nanoscale-ROS. COVID-19 patients with acute hypoxemic respiratory failure were treated with O 2 -containing nanobubbles because of their multimodal functions including antimicrobial, anti-inflammatory, drug-carrying capacity, and the promotion of wound healing (Afshari et al 2021 ). Inducing the viable but non-culturable state of pathogens (VBNC): VBNC is a unique state, which is a survival strategy for a number of bacteria under stressed and harsh environmental conditions.…”
Section: Cytotoxicity and Action Mechanisms Of Nanostructured Materia...mentioning
confidence: 99%